2018
DOI: 10.1016/j.jconrel.2018.06.013
|View full text |Cite
|
Sign up to set email alerts
|

A nanoformulation for the preferential accumulation in adult neurogenic niches

Abstract: Stimulation of adult neurogenesis by targeting the endogenous neural stem cells (NSCs), located in hippocampus and subventricular zone (SVZ), with nanoformulations has been proposed for brain repair in cases of neurodegenerative diseases. Unfortunately, it is relatively unknown the nanoformulation properties to facilitate their accumulation in the neurogenic niches after intravenous injection. Here, we have screened different gold-based formulations having variable morphology, surface chemistry and responsiven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 60 publications
0
28
0
Order By: Relevance
“…Furthermore, nanorods can be internalized more easily by cells as their increased surface allows them to interact more easily with receptors on the cell membranes [181]. AuNRs have been functionalized to increase their BBB delivery of angiopep-2 [71], RVG29 [105], CLPFFD [97] or transferrin [79]. In a study by Praça et al, AuNPs and AuNRs were functionalized with different amounts of transferrin and tested in vitro on a BBB model and in vivo on mice after intravenous administration [79].…”
Section: Inorganic Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, nanorods can be internalized more easily by cells as their increased surface allows them to interact more easily with receptors on the cell membranes [181]. AuNRs have been functionalized to increase their BBB delivery of angiopep-2 [71], RVG29 [105], CLPFFD [97] or transferrin [79]. In a study by Praça et al, AuNPs and AuNRs were functionalized with different amounts of transferrin and tested in vitro on a BBB model and in vivo on mice after intravenous administration [79].…”
Section: Inorganic Nanoparticlesmentioning
confidence: 99%
“…AuNRs have been functionalized to increase their BBB delivery of angiopep-2 [71], RVG29 [105], CLPFFD [97] or transferrin [79]. In a study by Praça et al, AuNPs and AuNRs were functionalized with different amounts of transferrin and tested in vitro on a BBB model and in vivo on mice after intravenous administration [79]. In vitro and in vivo results showed that AuNPs and AuNRs with a medium density of transferrin had the highest transport efficiency across the BBB, due to their lower avidity for the transferrin receptor.…”
Section: Inorganic Nanoparticlesmentioning
confidence: 99%
“…Since the BBB integrity is of primary importance for maintaining correct brain functioning, we assessed the impact of KBs on BBB permeability. To this end, BLECs were incubated with KBs for 48 h. To exclude the possibility that BLECs were not responsive to the damage possibly induced by KBs, we treated the human in vitro BBB model with mannitol, which is known to disrupt the BBB [40]. BBB permeability was checked by measuring the speed of diffusion of the small paracellular marker Lucifer Yellow (LY;~400 Da) across the BLEC monolayer to determine the endothelial permeability of Lucifer Yellow (Pe LY ).…”
Section: Kbs Do Not Affect the Viability And Integrity Of Blecsmentioning
confidence: 99%
“…13 Several NPs have been functionalized in order to target the receptors of the most common mediators such as transferrin (TfR), insulin and insulin-like growth factors, low-density lipoprotein, leptin, heparin-binding EGF and tumor necrosis factors, and glucose transporter. 13,24 Among the others, lipidic NPs are definitively one of the main nanostructures whose therapeutic efficacy was improved by an increase in BBB passage due to functionalization with specific ligands able to bind carriers or receptors. [25][26][27] It is worth to say that, in general, BBB crossing through CMT and RMT are nowadays well-known strategies and they have been extensively reviewed.…”
Section: Janus Particlesmentioning
confidence: 99%
“…AMT is another common strategy exploited to improve brain delivery, usually involving cationic proteins or cell penetrating peptides (CPPs). 13,24 In particular, CPPs are short amphipatic or cationic peptides (10/27 amino acids) that can enter the tissues in a non-invasive manner. 13,32 Although they could not provide brain selectivity, CPPs can be used to functionalize NPs, preventing brain efflux mechanisms and rapid degradation.…”
Section: Janus Particlesmentioning
confidence: 99%